Plant design for Gresbe Fertilizer Company (Ammonium Sulfate) - Fagela, Estrella B. (College of Engineering, 1961)
The proposed plant design for a fertilizer plant in the Philippines proposes to produce an annual output of 40,000 metric tons of ammonium sulfate. Costs studies reveals that with a capital investment of P23,000,000.00 and selling the product at P8.50 per bag (of 100 lbs), expect a profit of P6,790,000.00 before taxes and a profit of P2,735,620.00 after taxes annually, expect to recover the capital in eight years and five months.